Tatak Pilipino [episode no. 16] - Tropicana Studio (Malabon, Metro Manila). ([Quezon City ABS-CBN, 1991)
A uniquely Pilipino way and style.
[Episode no. 16] (50 min.). Rap music (10 min.) -- Mona Sulaiman in track and field sport (5 min.) -- Photojournalism (15 min.) --Karera (10 min.) -- Excerpts of an stage play by Rene Avellana (5 min.) -- Young Critic Circle (5 min.) -- [Episode no. 19] (50 min.) Names of the Philippines (5 min.) -- Pinoy Rock (15 min.) -- Apolinario Mabini (5 min.) -- Evolution of underwear (10 min.) -- Tropicana Studio in Malabon (10 min.) -- Pasyon (10 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Sulaiman, Mona; Mabini, Apolinario; Rap (Music).; News photographers -- Philippines; Horse-racing -- Philippines; Theater critics -- Philippines; Rock music -- Philippines; Underwear; Passion music; Philippines -- History